2015
DOI: 10.1016/j.canlet.2014.09.030
|View full text |Cite
|
Sign up to set email alerts
|

LPA-mediated migration of ovarian cancer cells involves translocalization of Gαi2 to invadopodia and association with Src and β-pix

Abstract: Lysophosphatidic acid (LPA) plays a critical role in the migration and invasion of ovarian cancer cells. However, the downstream spatiotemporal signaling events involving specific G protein(s) underlying this process are largely unknown. In this report, we demonstrate that LPA signaling causes the translocation of Gαi2 into the invadopodia leading to its interaction with the tyrosine kinase Src and the Rac/CDC42-specific guanine nucleotide exchange factor, β-pix. Our results establish that Gαi2 activates Rac1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 41 publications
5
36
0
Order By: Relevance
“…It is likely that the spatiotemporal coordination of signaling inputs from both of these α-subunits is involved in the invasive migration of ovarian cancer cells. Further, our observation that Gαi2-Rac as well as Gα13-Rho-mediated pathways are required for LPA mediated invasive migration of ovarian cancer cells [36, 42] as well as the independent findings that the migration mediated by CXCL12-CXCR4 signaling involves both Gαi2-mediated mTORC1 signaling [43] and Gα12/13 mediated Rho signaling pathways [14] supports this view.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…It is likely that the spatiotemporal coordination of signaling inputs from both of these α-subunits is involved in the invasive migration of ovarian cancer cells. Further, our observation that Gαi2-Rac as well as Gα13-Rho-mediated pathways are required for LPA mediated invasive migration of ovarian cancer cells [36, 42] as well as the independent findings that the migration mediated by CXCL12-CXCR4 signaling involves both Gαi2-mediated mTORC1 signaling [43] and Gα12/13 mediated Rho signaling pathways [14] supports this view.…”
Section: Resultssupporting
confidence: 59%
“…While these in vitro observations clearly implicate specific Gα-subunit(s), downstream of LPA-LPAR signaling, the identity of the Gα-subunit that could promote tumor growth in vivo has not been defined. Although Gαi-, Gαq-, and Gα12-family of proteins have been shown to transduce mitogenic as well as motogenic signals from LPARs in ovarian cancer cells [4, 35, 36], a comparative analysis to identify the Gα-subunit involved in stimulating ovarian cancer growth in vivo has not been undertaken until now. Therefore, in the present study, we examined the role of Gαi2, Gαq, Gα12, and Gα13 in ovarian cancer cell proliferation and migration in vitro and their tumorigenic role in xenograft tumors in vivo , by utilizing SKOV3 cells expressing nonspecific scrambled shRNA (SKOV3 NS) control cells and the respective Gα-silenced SKOV3 cells (shGαi2, shGαq shGα12, and shGα13).…”
Section: Introductionmentioning
confidence: 99%
“…FGF-1 induced fibroblast invasion, but not migration, whereas PDGF-AB and thrombin induced fibroblast migration, but not invasion. Of the mediators we found to induce invasion of primary mouse lung fibroblasts, PDGF-BB, EGF, and FGF-1 have been previously noted to induce invasion of fibroblasts isolated from other sources (32,(36)(37)(38), and LPA, FGF-1, and FGF-2 have been previously noted to induce cancer cell invasion (38)(39)(40)(41). Consistent with our finding that these mediators are able to induce fibroblast invasion ex vivo, we found evidence to suggest that these mediators all contribute to the non-cell-autonomous fibroblast invasion induced in vivo in the bleomycin model: knockdown of lung fibroblast PDGFRb, LPA 1 , EGFR, or FGFR2 expression each, by themselves, significantly decreased fibroblast invasion induced by BAL from bleomycin-challenged mice.…”
Section: Discussionmentioning
confidence: 75%
“…Recent reports from our lab [8, 15] have indicated that Src, via Gαi2, is involved in initiating invasive migration of ovarian cancer cells. Additionally, Src has been shown to activate HIF1α by diverse pathways involving both direct as well as indirect mechanisms [5355].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, defining a signaling node downstream of LPA-receptors has become critical to develop therapeutic strategy for inhibiting LPA-mediated oncogenic pathway(s). With this overarching goal, our laboratory as well as others have shown that the oncogenic activity stimulated by LPA involves the gep oncogenes Gα12 and Gα13 [14] as well as the putative gip2 oncogene Gαi2 [8, 15]. However, the role of these oncogenic Gα-subunits in the activation of specific LPA-mediated oncogenic responses is far from clear.…”
Section: Introductionmentioning
confidence: 99%